Carbon fluxes and budgets of intensive crop rotations in two regional climates of southwest Germany - Poyda, Arne; Wizemann, Hans-Dieter; Ingwersen, Joachim; Eshonkulov, Ravshan; Högy, Petra; Demyan, Michael S.; Kremer, Pascal; Wulfmeyer, Volker; Streck, Thilo (Agriculture, ecosystems & environment, 2019)
•High C losses from intensive crop rotations in southwest Germany.•C removals via harvest trigger SOC losses.•The recent increase in silage maize cropping threatens SOC stocks.•Growing bioenergy maize for CO2 mitigation seems questionable.•A re-diversification of crop rotations is needed to protect soil C stocks. The carbon (C) sequestration potential of croplands has recently become a subject of debate because it may contribute significantly to global climate change mitigation. By contrast, carbon dioxide (CO2) emissions from German croplands have continuously increased over the past decades as a result of soil organic carbon (SOC) losses. Contrasting results, however, have been obtained on the C sink or source function of European croplands based on long-term experiments and rather recent eddy covariance (EC) measurements. Over a period of eight years (2010–2017), we measured the net ecosystem exchange (NEE) of CO2 on six intensively managed cropland sites in two climatically different regions of southwest Germany (Kraichgau (KR) and Swabian Jura (SJ)) using the EC technique. Additionally, we measured aboveground crop biomass at three development stages and estimated management-related C inputs and exports. The inter-annual on-site variability of cumulated annual NEE was large, and neither the region nor the different sites significantly affected NEE budgets. Winter rapeseed showed the lowest CO2 uptake capacity among the observed crops, and the mean annual NEE in the years with winter rapeseed harvest was significantly lower compared to winter wheat, silage maize and winter barley. On average over 46 site-years, annual NEE showed a distinct CO2 uptake of −2580 kg CO2-C ha−1 yr−1. Considering management-related C fluxes, the resulting net biome productivity (NBP) indicated a C source function of the study sites with mean annual losses of 1190 kg C ha−1 yr−1. Due to high C removals after whole plant harvests, silage maize cropping resulted in significantly higher C losses of 4280 kg C ha−1 yr−1 compared to winter rapeseed, winter wheat and winter barley, with mean annual NBPs of 1430, −188 and −1340 kg C ha−1 yr−1, respectively. Consequently, a higher share of exported C in annual NBP resulted in higher C losses. We conclude that the recently increased importance of silage maize in crop rotations destabilizes SOC stocks, threatening the efforts in enhancing soil C sequestration. This calls for further investigations on the C sequestration potentials of more diverse crop rotations including perennial phases.